Analyzing Human Resource Governance Requirements from Perspective of Faculty Members at the Higher School of Management Sciences – Annaba (Journal of Economic Additions, 2026)
The study's goal is to find out what faculty members at the Higher School of Management Sciences in Annaba think are the most important things for good human resource management. The study's goals were met by using the descriptive-analytical method to gather data through a questionnaire sent to a group of faculty members. Consisting of 30 valid responses for analysis Statistical methods were applied using SPSS v26. The results of hypothesis testing showed that faculty members thought that governance requirements were met at high levels. This shows that they were very aware of and understood how important transparency, integrity, justice, and accountability are in human resource management practices to create a fairer work environment. The study suggests that these practices should be continued by setting up regular checks and evaluations of governance practices and broadening their scope to include different types of students and employees.Jel Classification Codes: G34, M12.
Keywords: Human Resource Governance; Integrity; Transparency; Justice; Social Responsibility